Implementation of Regional Innovation Policy as a Form of Public Service at the Surakarta City Population Administration and Civil Registration Office - Novyana Putri, Solichah (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to present the results of research on Regional Innovation Policy as a Form of Public Service at the Population Administration and Civil Registration Office of Surakarta City. This research uses empirical research types with descriptive research methods and qualitative approaches, equipped with primary data and literature data. The research location is at the Surakarta City Population Administration and Civil Registration Office. The results showed that policies related to regional innovations made by the Surakarta City Population Administration and Civil Registration Office are to create various innovations that facilitate public services, especially population document services including Dukcapil Dalam Gripan, Ball Pickup Service, SAPU KUWAT (One Package of Citizen Population Affairs Fulfilled), LANTATUR (Service Without Descending), BESUK KIAMAT (Condolences Send Death Certificate), and Clear MY BELOVED'S FOREHEAD. This shows that the Surakarta City Population Administration and Registration Office has provided ease of service to the community through several innovations so as to improve effective and accurate community data